2021
DOI: 10.48078/publetters.v1i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Masalah publikasi ilmiah di lingkup Sekolah Tinggi Teologi Kristen Indonesia

Abstract: The research is focused on seeing the causes of the low performance of lecturers and students in Christian Religious Colleges (PTKK). The three main things that were discussed and analyzed as the root of the problem were the lack of publication awareness, lack of support for infrastructure and funds, and minimal research awareness. Therefore, if PTKK does not immediately present a solution for these three aspects, PTKK will be left behind and eliminated from global competition. PTKK is required to carry out re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…In the last three years, there has been a kind of awakening of consciousness to conduct publications in Christian religious colleges. Lecturers get a wide-open actualization space, penetrating local, even national boundaries [9]. Online publication media provides an opportunity for everyone to become a theologian recognized by the international world [10].…”
Section: B Ethical Virtue Of Doing Theologymentioning
confidence: 99%
“…In the last three years, there has been a kind of awakening of consciousness to conduct publications in Christian religious colleges. Lecturers get a wide-open actualization space, penetrating local, even national boundaries [9]. Online publication media provides an opportunity for everyone to become a theologian recognized by the international world [10].…”
Section: B Ethical Virtue Of Doing Theologymentioning
confidence: 99%
“…Technological developments are increasingly challenging religious leaders because the 21st century is a time that challenges human thinking, especially in understanding and explaining things related to God [1]. In a survey conducted by the Varkey Foundation globally in 2017 about the important factors of happiness for Generation Z (18-21 years), it was found that 93% of Generation Z in Indonesia made a commitment to religion as the most important factor in happiness.…”
Section: Introductionmentioning
confidence: 99%
“…Hal yang sangat terlihat dalam budaya ini adalah perkembangan teknologi yang cepat dan tanpa batas serta perubahan pemikiran masyarakat yang semakin kritis dan analitis (Wijaya, 2023). Kemudahan dan kecanggihan teknologi yang hampir tanpa batas membuat kecenderungan manusia untuk tergantung dengan teknologi dan menghasilkan cara berpikir manusia yang mengarah pada pragmatisme, dan menerima kebenaran berdasarkan pengetahuan atau akalnya, meringkas dan menyederhanakan berbagai hal yang terasa rumit, bertele-tele dan yang dirasa mengganggu efektivitas dan efisiensi dalam kehidupan (S. E. Zaluchu, 2009).…”
unclassified